Boundaries, Identities and Territoriality: Seven Shi‘i Villages as a Case Study - Kaufman, Asher (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2005)
This study explores the history of seven Shi‘i villages in mandatory Palestine, since the end of World War I. Specifically, it examines the villagers’ relations with the Jewish population and the Sunni-Arab population between 1924-1948 and, their status as Palestinian refugees in Lebanon (1948-1994), and their new civic identity following the naturalization bill of 1994, which granted them Lebanese citizenship. To fathom the shifts in territorial identity and border politics, the tale of the seven villages is examined from three perspectives: that of the villagers, the Palestinian perspective, and the Lebanese perspective. The different narratives shed light on the colonial heritage in the Middle East, regional boundaries and the formation of national identities, and contemporary domestic politics in Lebanon.